2010
DOI: 10.1039/b916877j
|View full text |Cite
|
Sign up to set email alerts
|

Cation and anion selectivity of zwitterionic salicylaldoxime metal salt extractants

Abstract: 3-Dialkylaminomethyl substituted salicylaldoximes are efficient metal salt extractants, and, in contrast to related "salen"-based reagents, are sufficiently stable to acid hydrolysis to allow commercial application in base metal recovery. Crystal structures show that metal salts are bound by a zwitterionic form of the reagents, with copper(II) nitrate, tetrafluoroborate and trifluoroacetate forming [Cu()(2)X(2)] assemblies in a tritopic arrangement with a trans-disposition of the anions outwith the coordinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 22 publications
3
33
0
2
Order By: Relevance
“…1 A critical role for anion recognition is either recognized or proposed in a number of industrial processes, such as nuclear waste extraction and remediation, 2 as well as base and precious metal extraction. 3 Special attention has been given to metal-containing anion receptors as the metal centre can play a crucial structural role in organizing anion-binding groups into a geometry appropriate for the recognition of a specific anion. 4-6 Furthermore, electrostatic interactions between the targeted anion and a Lewis acidic metal centre can promote a binding event.…”
Section: Introductionmentioning
confidence: 99%
“…1 A critical role for anion recognition is either recognized or proposed in a number of industrial processes, such as nuclear waste extraction and remediation, 2 as well as base and precious metal extraction. 3 Special attention has been given to metal-containing anion receptors as the metal centre can play a crucial structural role in organizing anion-binding groups into a geometry appropriate for the recognition of a specific anion. 4-6 Furthermore, electrostatic interactions between the targeted anion and a Lewis acidic metal centre can promote a binding event.…”
Section: Introductionmentioning
confidence: 99%
“…Average of two crystallographically independent values present in metal complex dimer [Cu(L 6 ) 2 ] 2 (see Figure 5). 12 c No esd values for positional parameters are provided for H-atoms in these structures 9,11 The strengths of the H-bonds in [ The effects of an aminomethyl group substitution in the 3-position on the structures of complexes in the solid state were evaluated by comparing the single crystal X-ray structures of…”
Section: Dft and X-ray Structurementioning
confidence: 99%
“…The oximic -OH and phenolate Oatoms, as well as the non-protonated tertiary amine N-atoms, form intermolecular hydrogen bonds throughout 5 ( Figure 5). The presence of these H-bonds within the copper dimers of oxime-based ligands was reported in 2010 by Tasker et al 21 In 2002, Kandaswamy and coworkers reported the binuclear copper and nickel complexes of L 4a with a different metal coordination pattern from the pattern observed in the complex 5. 20 Table 3.…”
Section: Such Interactions Have Been Observed In the Complexes Bis(5-mentioning
confidence: 72%
“…Tasker et al reported metal complexes of salicylaldoxime-based ligands where the tertiary amines are similarly involved in oxime-to-phenolate hydrogen bonds (hydrogen-to-acceptor distances 2.052(2) Å and 2.154(2) Å) and oxime-to-piperidino hydrogen bonds (hydrogen-toacceptor distance 2.119(3) Å and 2.249(2) Å). 21 In the Tasker example all the tertiary nitrogen atoms are H-bond acceptors with the oxime hydroxyl groups; none of them are protonated. However, when the orientation of the structure precludes (tertiary)N···H(oxime) contacts and interactions with nearby acceptors (e.g., counterions such as X -, NO 3 -, BF 4 -) are possible, then the tertiary nitrogen atoms are generally protonated and the system is stabilised by (tertiary)N-H···Acceptor(counter ion) hydrogen-bonding interactions.…”
Section: Resultsmentioning
confidence: 99%